2014
DOI: 10.20884/1.jdh.2014.14.2.295
|View full text |Cite
|
Sign up to set email alerts
|

Pengawasan Kinerja Advokat Dalam Pemberian Bantuan Dan Pelayanan Jasa Hukum (Studi Di Jawa Tengah)

Abstract: The performance of advocate simply defined as the effectiveness of the services provided by advocates and efficiency of resources allocated and used to prepare such services. There are several reasons that make the effectiveness of the performance advocate can not be determined as exact. Research that seeks to find and locate the causes of the use of empirical legal research methods with sociological and  economics approach. The indicators of performance can be classified into several types, namely efficiency,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Moreover, the performance of advocate which refuse to provide law assistance for poor people and the tortuous bureaucracy to get them, make justice acquisition in Indonesia is worse [17] Drugs abuse has a large and complex dimension, either from medical, psychiatric, mental health, or psychosocial aspect [23]. Drug addict and abuser are "sick people".…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the performance of advocate which refuse to provide law assistance for poor people and the tortuous bureaucracy to get them, make justice acquisition in Indonesia is worse [17] Drugs abuse has a large and complex dimension, either from medical, psychiatric, mental health, or psychosocial aspect [23]. Drug addict and abuser are "sick people".…”
Section: Resultsmentioning
confidence: 99%
“…Previous research showed that the addition of EDTA to HCl solution could also act as an inhibitor, preventing scale formation on equipment [19]. Furthermore, the presence of additives acting as inhibitors can keep the cation-anionforming scales in the solution [26]. For example, tartaric acid, when used as an additive, shows the ability to inhibit the growth of barium sulphate as the crystal structure formed causes difficulty in adhering to the equipment [6].…”
Section: Acidizing Treatment Using Hcl Andmentioning
confidence: 99%
“…15 Ruang lingkup tugasnya memiliki jangkauan lebih luas, namun secara power atau kekuatan tidak lebih superior dibandingkan penegak hukum lainnya. 16 Dalam pelaksanaan tugasnya, advokat dijamin dan dilindungi oleh hukum, sehingga meminimalisir tindakan pihak lain untuk melakukan tekanan, ancaman, hambatan, atau perlakuan merendahkan harkat dan martabat profesinya tersebut.…”
Section: B Rumusan Masalahunclassified